VISUALIZING THE CONTROL ALGORITHM FOR FOUR MECANUM WHEELS - Котвицький, А.Т.; Горенко, Д.В. (SWorldJournal, 2024)
This paper explores an innovative rectangular moving platform equipped with four mecanum wheels, enabling it to move in any specified direction. Mecanum wheels are particularly valuable in robotics for their maneuverability and precise control.The aim o